The Oxidative Drug Combination for Suppressing KRAS G12D Inducible Tumour Growth. (30th December 2022) - Begimbetova, Dinara; Kukanova, Assiya; Fazyl, Fatima; Manekenova, Kenzhekyz; Omarov, Talgat; Burska, Agata N.; Khamijan, Medina; Gulyayev, Alexandr; Yermekbayeva, Bakytgul; Makishev, Abay; Saliev, Timur; Batyrbekov, Kanat; et al.
Abstract : Background. Kirsten rat sarcoma (KRAS) protein is an essential contributor to the development of pancreatic ductal adenocarcinoma (PDAC). KRAS G12D and G12V mutant tumours are significant challenges in cancer therapy due to high resistance to the treatment. Objective. To determine how effective is the ATO/D-VC combination in suppression of PDAC the mouse transgenic model. This study investigated the antitumour effect of a novel combination of arsenic trioxide (ATO) and D-ascorbic acid isomer (D-VC). Such a combination can be used to treat KRAS mutant cancer by inducing catastrophic oxidative stress. Methods. In this study, we examined the effectiveness of ATO and D-VC on xenograft models—AK192 cells transplanted into mice. Previously, it has been shown that a high concentration of Vitamin C (VC) selectively can kill the cells expressing KRAS. Results. The results of this study demonstrated that the combination of VC with a low dose of the oxidizing drug ATO led to the enhancement of the therapeutic effect. These findings suggest that the combined treatment using ATO and D-VC is a promising approach to overcome the limitation of drug selectivity and efficacy.